The Latest Developments in the Crime of Aggression in International Law - Mohsen Ghadir; Mohamdreza Rashnavadi (پژوهشهای حقوقی)
The crime of territorial aggression is among the most terrible international crimes. After the outbreak of World War II, the Allies decided to try the defeated Axis of this war, including on charges of crimes against peace. After seventy years since the last and only case of the crime of aggression was prosecuted in an international criminal court, the jurisdiction of the International Criminal Court was activated in July 2018 over the crime of aggression. The explanation of the way to activate the jurisdiction of the court and its fruition since the drafting of the statute followed a winding path and lasted for two decades. The 16th session of the General Assembly of the International Court of Justice started on the 4th of December at the headquarters of the United Nations in New York with the speech of the Secretary General of the United Nations and ended on the 14th of December. The most important achievement of the 16th summit was the activation of the International Criminal Court's jurisdiction over the crime of "Territorial aggression". we seek to investigate the latest developments in the crime of aggression in international law using a descriptive-analytical method.